2012
DOI: 10.1002/ar.22526
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Environment and White Matter in Aging Brain

Abstract: Normal aging is commonly associated with decreased cognitive functions, which could be conspicuously alleviated by enriched environment (EE) with physical, social, and sensory stimuli, suggesting that aging brain still has intriguing plasticity. Multiple researches have been carried out to explore the structural and the molecular changes in aging brain, which would be considered for evidences that EE regulated brain plasticity. Because there is no significant neuron loss in aging cerebral cortex and the white … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 103 publications
0
13
0
1
Order By: Relevance
“…Several studies have reported that learning and motor activity influence oligodendrocytes and myelination in white and grey matter of the adult brain [8, 12, 13, 29, 35, 52, 55, 56]. In particular, enriched environment increases myelin-forming oligodendrocytes, myelinated axons and white matter volume during brain aging [47, 48, 57, 59].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that learning and motor activity influence oligodendrocytes and myelination in white and grey matter of the adult brain [8, 12, 13, 29, 35, 52, 55, 56]. In particular, enriched environment increases myelin-forming oligodendrocytes, myelinated axons and white matter volume during brain aging [47, 48, 57, 59].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the effects of enriched/impoverished environment can be age-dependent [4,28,36]. However, enriched environment can be beneficial even in adult animals, as it has been described in several injury models and conditions [37,38]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the number of oligodendrocytes decreases in an age-dependent manner (Jinno, 2015). As a result, the efficiency of remyelination is significantly reduced in the aged brain (Yang et al, 2012). In addition, a decline in axonal regeneration and functional recovery in injured older animals is associated with loss of extracellular matrix components, neurotrophic factors, and intrinsic feedback mechanisms (Roozbehi et al, 2015).…”
Section: Age-related Changes In the Cnsmentioning
confidence: 99%